Core-shell 3D printed biodegradable calcium phosphate cement—Alginate scaffolds for possible bone regeneration applications - Schweiker, Clara; Zankovic, Sergej; Baghnavi, Anna; Velten, Dirk; Schmal, Hagen; Thomann, Ralf; Seidenstuecker, Michael (Frontiers in Drug Delivery, 2024)
The core/shell 3D printing process using CPC and alginate is intended to create biodegradable scaffolds that have a similar stability to bone tissue and also offer sufficient and continuous antibiotic release. In this way, a patient-specific and patient-friendly process will be established, which should optimally support the human organism in its regeneration. To generate the best possible strength values, the printed scaffolds underwent various post-treatments and were then tested in a material test. The test methods included self-setting, storage in a drying cabinet with a water-saturated atmosphere at 37 °C, followed by incubation in PBS, freeze-drying, and coating the samples with alginate. Additionally, a degradation test at pH 7.4 and pH 5 was carried out to test stability under in vitro conditions. It was shown that the untreated and freeze-dried samples failed at a maximum load of 30-700 N, while the remaining scaffolds could withstand a load of at least 2000 N. At this failure load, most of the test series showed an average deformation of 43.95%. All samples, therefore, remained below the strength of cancellous bone. However, based on a 20% load after surgery, the coated scaffolds represented the best possible alternative, with a Young’s modulus of around 1.71 MPa. We were able to demonstrate that self-setting occurs in core-shell printed CPC/alginate scaffolds after only one day, and that mass production is possible. By coating with alginate, the compressive strength could be increased without the need for additional post-treatment. The mechanical strength was sufficient to be available as a scaffold for bone regeneration and additionally as a drug delivery device for future applications and experiments.